Conventional Cultivated Forage Production and Utilization in the Ethiopian Highlands - Bezabih, Melkamu; Adie, Aberra; Assefa, Getnet; Mekonnen, Kindu; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training on Livestock Feed and Forage Innovations